A pilot study on exertional tasks with physiological measures designed for the assessment of military concussion - Julianna H Prim; Maria I Davila; Karen L McCulloch (Concussion)
Background: Guidelines for clinicians treating military concussion recommend exertional testing before return-to-duty, yet there is currently no standardized task or inclusion of an objective physiological measure like heart rate variability (HRV). Methodology & results: We pilot-tested two clinically feasible exertional tasks that include HRV measures and examined reliability of a commercially available heart rate monitor. Testing healthy participants confirmed that the 6-min step test and 2-min pushup test evoked the targeted physiological response, and the Polar H10 was reliable to the gold-standard electrocardiogram. Conclusion: Both tasks are brief assessments that can be implemented into primary care setting including the Polar H10 as an affordable way to access HRV. Additional research utilizing these tasks to evaluate concussion recovery can validate standardized exertional tasks for clinical use.